Agronomic performance and productivity of Arabica coffee intercropped with timber species - de Freitas, Ana Flávia; Fonseca, Arley José; Marin Lordelo Volpato, Margarete; Rodrigues Carvalho, Gladyston; Pereira Venturin, Regis; Silva, Vânia Aparecida (Revista Ceres, 2023)
The insertion of the tree component in coffee production is a strategy from an economic and environmental perspective. Thus, the objective of this study was to evaluate the temporal influence on the agronomic and productive performance of the coffee crop under the interference of different tree species as a function of spacing. The experiment was set in the municipality of Santo Antônio de Amparo-MG, in 2012, and conducted in a randomized block design with four replications. The treatments were: cultivar ‘Catuai Vermelho IAC 99’ in monoculture (3.40 m x 0.65 m) and intercropped with African mahogany, teak and pink cedar, in two spacings (9 x 13.6 m and 18 x 13.6 m), in coffee rows. Three coffee rows were fixed between rows, totaling 13.6 m. The following variables were evaluated: height (m), stem diameter (cm), crown diameter (m), productivity (bags ha-1) and yield (l/sc) for coffee. From the evaluations, there is a significant effect of height, productivity and yield for the coffee crop. The system intercropped with tree species did not influence coffee productivity and yield until the 3rd harvest and, for the 5th harvest, intercropping with mahogany favored productivity, although the accumulated productivity did not show any treatment effect.